Berlusconi e Macron: figure per esplorare l’ipermoderno Un’analisi de Il Duca di Mantova di Franco Cordelli e Un personnage de roman di Philippe Besson (Altre Modernità, 2021)
The article analyses Franco Cordelli's Il Duca di Mantova and Philippe Besson's Un personnage de roman. In these texts, the authors compare themselves with the figure of Silvio Berlusconi and Emmanuel Macron respectively. Through the category of 'hypermodern', the article intends to study some traits of contemporary power: first of all, it will analyse the ontological status of the texts and the ways used to mix fictional elements with real data; then, it will show which images of power emerge from the two represented politicians; in conclusion, going beyond the texts, it will try to define the concept of 'Leviathan-hologram', in order to provide new conceptual tools to deconstruct the contemporary political imaginary.
Keywords: Franco Cordelli; Philippe Besson; Il Duca di Mantova; Un personnage de roman; Hypermodernity; Power